Effectiveness Change Management Improving MSMEs Performance Kediri, Labuhan Batu, Kampar Mine Rope - Anita Sumelvia Dewi; Imam Mukhlis (Formosa Journal of Science and Technology, 2023)
The level of success of MSMEs in carrying out tasks to achieve goals within a certain period of time is called MSME performance. By using a change management management program adopted based on existing knowledge, Kediri, Labuhan Batu, and Kampar rope mining MSMEs can improve the performance of employees and MSMEs to achieve MSME goals. In this way, Kediri, Labuhan Batu, and Kampar rope mining MSMEs can gain an increase in income of 20% in 2023. With proper change management, the performance of all employees can be improved so that MSMEs can achieve their goals. Because of the reciprocal relationship between MSMEs and society, MSMEs must also develop along with society. Change management in Kediri, Labuhan Batu, and Kampar rope mining MSMEs requires appropriate policies to achieve service goals, profit receipt and MSME performance. This policy includes establishing a change agent, establishing a performance manager, managing risk management, and activities to monitor and assess the implementation of change management. This is done to improve employee performance so that they can achieve common goals.